(untitled) (Latin-American Journal of Computing, 2020)
The growing development of the Internet of Things (IoT) has diversified its fields of application, improving not only the interconnection of people but as well the communication between industrial machinery (M2M, Machine-to-Machine), in which its features in range, scalability, and low cost of deployment can be taken advantage of. LoRa and LoRaWAN technologies are presented as one of the main low-cost wireless communication options in the integration of industrial systems with a view to the new requirements of Industry 4.0. In this work, a measurement campaign and the analysis of the data obtained were performed to evaluate the behavior and applicability of LoRa and LoRaWAN technologies within industrial environments. To contrast the results, tests were performed in clear urban environments, where it was observed that the conditions inside the industrial buildings allow the establishment of a link with favorable radio frequency conditions. Initially, short-range scenarios (<100 m) have been considered in which a line of sight is maintained between the transmitter and the receiver.